Exposure study to examine chemosensory effects of ɛ-caprolactam in healthy men and women - Triebig, Gerhard; Triebig-Heller, Isabel; Bruckner, Thomas (Inhalation toxicology, 2016)
Context: ε-Caprolactam is an important industrial chemical with a relatively low human toxicity; of importance is the irritations that occur after exposure to ε-caprolactam as aerosols or vapors.Objective: The aim of this study was to examine symptoms and objective effects, which occur on the mucous membranes of the eyes and the upper respiratory tract.Methods: A total of 52 healthy volunteers (26 women and 26 men, aged between 19 and 50 years) were exposed by random to different ε-caprolactam concentrations (0.05, 0.5 and 5.0 mg/m³) and the control condition (0.0 mg/m³) for 6 h on four consecutive days. Eye blinking frequency, tear film break-up time, eye redness, nasal flows and resistance, olfactory function as well as total protein and interleukin-8 in nasal lavage fluid were determined daily before, during and after exposure. Questionnaires were used to record both subjective symptoms and personality factors.Results: There were no significant specific effects on the subjective and objective endpoints examined. Statistical analysis yielded no evidence of concentration-response relationships. Evaluation of olfactory symptoms showed that the duration of the stay in the chamber and not the ε-caprolactam concentration was decisive for the perception of “impure air”. Personality factors had no significant influence on the reported symptoms.Conclusions: Exposure to ε-caprolactam concentrations of 5.0 mg/m³ at maximum for 6 h did not cause chemosensory effects on the upper respiratory tract or eyes of healthy volunteers. Therefore, the concentration of 5.0 mg/m³ corresponds to the No Observed Adverse Effect Level (NOAEL).